Malang Creative Fussion as a Facilitator of Malang Creative Community in Supporting the Achievement of the 9th SDGs Goal - Yekti, Septian Nur; Latifah, Latifah; Larasati, Dinda (Global Local Interactions: Journal of International Relations, 2019)
In October 2015, the United Nations (UN) proclaimed Sustainable Development Goals (SDGs) which then becomes the guideline of more sustainable development programs in the member states. It consists of 17 targets in the field of security, politics, economy, and environment. This paper focuses on the implementation of 9th goal: Infrastructure, Industry, and Innovation, by analyzing the connection between the goal with Malang Creative Fussion (MCF) program in Malang, one city in Indonesia. This paper aims to explain the learning process in MCF that facilitates the realization of creative economic ecosystem in Malang. In doing so, this paper employs field research with descriptive method and intermestic approach as the tool of analysis. Intermestic approach sees how internatinal norms, values, ideas, and principles influence the policies and phenomenon in domestic level and the opposite. With capilarity concept as the part of intermestic, it explains the learning process and actors in the connected areas and its impact. Finally, this paper finds that MCF programs implements the principles of the 9th goal with some domestic modified nature and run by some intellectual actors in learning process. The program so far can reach the goal of the SDGs’ 9th goal in Malang.